Development of a Strategy for Independent Village Development Based on IDM Predictions Using Linear Regression: A Study of Bi'ih Village, South Kalimantan - Artamevia, Mima; Lubis, Muharman; Mukti, Iqbal Yulizar (Jurnal Teknik Informatika (Jutif), 2025)
Village development in Indonesia still faces inequality due to uneven utilization of technology, resulting in many villages lagging behind economically despite their strong social and environmental potential. This study aims to predict the status of the Village Development Index (IDM) of Bi’ih Village in 2025 and formulate development strategies toward an independent village through the integration of information technology and local wisdom. The method used is linear regression analysis of IDM data from 2017 to 2024, followed by a gap analysis comparing the achievements of Bi’ih Village with those of 11 self-reliant villages in Karang Intan Subdistrict. The prediction results show that the IDM value of Bi’ih Village in 2025 will be 0.7744, placing it in the Advanced category, 0.0411 points below the Independent threshold (>0.8155). The Social Resilience Index (IKS = 0.8782) and Environmental Resilience Index (IKL = 0.8388) have exceeded the Independent threshold, while the Economic Resilience Index (IKE) remains low at 0.6061. The main constraints include limited access to digital markets, manual financial record-keeping, and low digital literacy among village entrepreneurs. The novelty of this research lies in the formulation of a development strategy based on the integration of ICT and local wisdom, with a focus on strengthening digital BUMDes, implementing integrated financial systems, developing upstream–downstream partnerships, and branding local products. This approach demonstrates that digitalization rooted in local wisdom can enhance economic productivity, strengthen resilience, and support sustainable progress toward independent-village status.